From transactions to cooperation: Developing supply chain of ancient grains between relationships and joint interests. Issue 5 (8th November 2019) - Casalegno, Cecilia; Migheli, Matteo; Bonfanti, Angelo; Maple, Peter
Abstract : Purpose: The purpose of this paper is to add understanding to whether the supply chain (SC) of ancient grains, einkorn in particular, may activate the virtuous mechanisms that enable pursuing a new equilibrium based on relationships and joint interests. Design/methodology/approach: This study adopts the single case study as a methodological approach. More precisely, it focusses on the SC of ancient grains in Piedmont (Italy) examining in detail Mulino Marino. Interviews with the management of this single player and to some farmers' local associations were carried out. Findings: The einkorn SC in Piedmont Region is an interesting case of short, local and direct SC because it aims at delivering a product that is more sustainable in terms of production, nutritional values and properties. In addition, this study confirms previous studies according to which for an effective supply chain management (SCM) it is important to implement the following conditions: the right equilibrium among SC players' physiologically conflicting interests, players' integration and transparent information among all the SC stakeholders, including final consumers. Practical implications: The study offers implications for food managers involved in the (short) SCM. Originality/value: Elements of originality can be identified in this research to the extension of studies on SCM in the ancient grains industry.